2015
DOI: 10.3892/mmr.2015.4379
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone suppresses the proliferation and induces the apoptosis of pancreatic cancer cells via the STAT3 signaling pathway

Abstract: Abstract. Pancreatic cancer remains a challenging disease worldwide. Cryptotanshinone (CPT) is one of the active constituents of Salvia miltiorrhiza Bunge and exhibits significant antitumor activities in several human cancer cells. However, the efficacy and molecular mechanism of CPT in pancreatic cancer remains to be elucidated. In the present study, the effect of CPT on the proliferation, apoptosis and cell cycle of human pancreatic cancer cell BxPC-3 cells was evaluated. The results demonstrated that CPT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…CTS, as a main active component isolated from the root of Salvia miltiorrhiza Bunge, has been reported to possess a great antiproliferation effect on different cancer cells. 22, 29, 30, 31 In the present study, we confirmed that CTS could significantly inhibit the proliferation of MGs cells in vitro and the growth of intracranial tumor in vivo . The survival period of nude mice bearing intracranial U87 xenografts was obviously extended.…”
Section: Discussionsupporting
confidence: 81%
“…CTS, as a main active component isolated from the root of Salvia miltiorrhiza Bunge, has been reported to possess a great antiproliferation effect on different cancer cells. 22, 29, 30, 31 In the present study, we confirmed that CTS could significantly inhibit the proliferation of MGs cells in vitro and the growth of intracranial tumor in vivo . The survival period of nude mice bearing intracranial U87 xenografts was obviously extended.…”
Section: Discussionsupporting
confidence: 81%
“…Among them, cryptotanshinone (CPT) has been demonstrated to have bioactivities including anti-inflammatory, anti-oxidative stress and antiplatelet aggregation properties (9). Previously, increasing evidence indicates that CPT appears to exert diverse anticancer properties against numerous human cancer cell lines, such as prostate cancer (10), leukemia (11), gliomas (12), hepatic carcinomas (13), pancreatic (14), breast (15), colorectal (16) and melanoma cancer (17). However, only a few studies have reported the anticancer effects of CPT on lung cancer, and more importantly, the underlying mechanism is largely unknown.…”
Section: Cryptotanshinone Inhibits Cellular Proliferation Of Human Lumentioning
confidence: 99%
“…Other benefits of Salvia miltiorrhiza include antibacterial (23), immunomodulatory (24) and antioxidant (25) activities. One of the main components of Salvia miltiorrhiza, Cryptotanshinone (CT), has been evaluated in vitro and in vivo as anticancer treatment in human tumor cell lines from different origins, such as, prostate (18,26), breast (26,27,28,29) hepatic (30) and colorectal (18,30,31,32), lung (33), pancreatic (34), kidney (35), glioma (36) and ovarian (37). To date, several human studies have highlighted significant apoptotic effects of CT treatment in cancer cell lines using concentrations of 5 -50 Ī¼M (28,32,33,34).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main components of Salvia miltiorrhiza, Cryptotanshinone (CT), has been evaluated in vitro and in vivo as anticancer treatment in human tumor cell lines from different origins, such as, prostate (18,26), breast (26,27,28,29) hepatic (30) and colorectal (18,30,31,32), lung (33), pancreatic (34), kidney (35), glioma (36) and ovarian (37). To date, several human studies have highlighted significant apoptotic effects of CT treatment in cancer cell lines using concentrations of 5 -50 Ī¼M (28,32,33,34). Other effects of CT included cell cycle arrest at G1/G0 phase (30,34,38), and at G2/M phase (33,36,39), inhibition of Cyclin D1 protein expression in different types of cancer (18,31,33,34,35), and downregulation of matrix metallopeptidases (MMP-2/MMP-9), which are responsible for cell invasion and metastasis (37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation